PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) YANG DIBERI KOMPOS TANDAN KOSONG KELAPA SAWIT - Nurmayulis Nurmayulis; Putra Utama; Assad Syah B. Pohan (Jurnal Agroekoteknologi, 2014)
This research aims to know the influence of the granting of the empty Palm bunches compost on the growth of seedlings of the oil palm (Elaeis guineensis Jacq.) in the nursery. This research has been done in the Banjar Agung village, Sub-district of Banjar Jaya, Serang Banten in May until July 2013. This study used a randomized blocked design (RAK) with a single factor and 5 treatment namely: M0 (0 g Compost), M1 (33 g Compost), M2 (67 g Compost), M3 (100 g Compost), M4 (133 g Compost). Every treatment repeated 5 times, so that the obtained 25 units of the experiment. The parameters observed were higher plants (cm), stem diameter (mm), broad-leaf (cm2), root dry weight (g) and dry weight (g). The research results showed that treatment empty Palm bunches composting gives a very real significant influence for plant height, while diameter of stem, leaf area, dry weight, and root dry weight berangkasan gives no real significant influence on the growth of oil palm seeds.